GeneChip Analyses of Global Transcriptional Responses of Murine Macrophages to the Lethal Toxin of Bacillus anthracis - Comer, Jason E. (American Society for Microbiology, 2005)
We performed GeneChip analyses on RNA from Bacillus anthracis lethal toxin (LeTx)-treated RAW 264.7 murine macrophages to investigate global effects of anthrax toxin on host cell gene expression. Stringent analysis of data revealed that the expression of several mitogen-activated protein kinase kinase-regulatory genes was affected within 1.5 h post-exposure to LeTx. By 3.0 h, the expression of 103 genes was altered, including those involved in intracellular signaling, energy production, and protein metabolism.